The Influence of Price Perception and Electronic Word of Mouth on Fashion Product Purchase Decisions through Customer Value in Generation Z of Tiktokshop Users in Surabaya - Fannyza Aliefvia Azzahra; Maharani Ikaningtyas (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to analyze the influence of price perception and Electronic word of mouth (e-WOM) on the product purchase decision fashion on TikTok Shop with Customer Value as an intervening variable in Generation Z in Surabaya. A quantitative approach was used by collecting data through questionnaires to 157 respondents and analyzed using SEM-PLS with the help of SmartPLS 4. The results of the study show that price perception and e-WOM have a positive and significant effect on purchasing decisions and Customer Value, and Customer Value have a positive and significant effect on purchasing decisions. In addition, Customer Value proven to mediate the influence of price perception and e-WOM on purchase decisions, so that purchase decisions are not only directly determined by these two variables, but also through the value perceived by consumers.